Wideband (22-30ghz) mm-wave substrate integrated waveguide (siw) antenna for 5g application - AL-Fadhali, Najib; A Majid, Huda; Omar, Rosli; Rahim, M. K. A.; Shah, S. M.; Esmail, B.A.F (2019)
In this paper, the SIW cavity slots antenna wideband millimeter-wave is proposed for fifth generation (5G) communication. The antenna also shows an average gain of 8,574 dBi, 20 x 20 mm2 compact. The proposed antenna applies to 5G application at 28 GHz operating frequency. The simulated results show that the SIW antenna resonates throughout the 22 GHz to 30 GHz bands to cover all applications within this range. The coefficients of reflection in all ranges from 22 GHz to 30 GHz are below 10 dB. At 28 Ghz, high efficiency and outstanding gain of the antenna is achieved